Molecular Analysis and Genotyping of Drug-Resistant Acinetobacter baumannii Isolates from Clinical Specimens - Muhammed Ameen, Sirwan M.; Rasool, Aram H. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2025)
Acinetobacter baumannii is a globally concerning hospital infection because it has developed resistance to many antibiotics, including last-resort carbapenems. In this study, 46 non-duplicate A. baumannii isolates from hospitalized patients are identified by the Phoenix BD Diagnostic System, which are used for bacterial identification and antimicrobial susceptibility profiles. Various clinical specimens, including endotracheal aspiration, urine, wound, blood, burns, and cerebrospinal fluid, were collected between 2023 and 2024 at different hospital wards. To provide further understanding of the epidemiology of multidrug-resistant (MDR) A. baumannii isolates, this study attempts to; (1) utilize enterobacterial repetitive intergenic consensus polymerase chain reaction (ERIC-PCR) DNA fingerprinting to estimate genetic diversity, which reveals a significant level of genetic relationship is established amongst A. baumannii isolates from hospitalized patients, suggesting cross-transmission, and (2) clarifies the genetic characteristics of the antimicrobial resistance profiles contributing to the antibiotics widely used for MDR A. baumannii isolates. All isolates are classified as MDR (54.3%), extensively drug-resistant (39.1%), and pandrug-resistant (6.5%). According to Clinical and Laboratory Standards Institute-2024 standards, 93.4% and 91.3% of isolates are resistant to meropenem and imipenem, respectively, while colistin and tigecycline are the most effective antibiotics. Furthermore, the most common of the genes present among clinical isolates are blaOXA-51 (100%) and pmrC (97.80%), while the less common detected genes are blaIMP (0.0%) and blaOXA-58 (46%). ERIC-PCR could provide a rapid and dependable scheme to recognize clonal relationships among isolates from a multiplicity of clinical samples. Controlling endemic A. baumannii strains, particularly in intensive care unit settings, is essential.